Consumo de sustancias psicoactivas y su relación con la funcionalidad familiar en los residentes de la comunidad terapéutica del Municipio de Loja - Cartuche Sanmartín, Sandra Maribel (2020)
Consumption of psychoactive substances increases every day, and these can cause health repercussions both for the person who uses them as for the people around them, causing damage in the family functionality, the same that plays a fundamental role when facing and overcoming each of the problems that arise. Therefore, the fundamental purpose of this research was to determine the relation between the consumption of psychoactive substances and family functionality in the residents of the therapeutic community of the Municipality of Loja, identifying the sociodemographic characteristics of the study population, setting the type and frequency of psychoactive substances that they consume and proving the level of family functionality of the study population. The research corresponds to a quantitative focus with a non- experimental design. Its scope is descriptive, correlational, and cross- sectional. For this study took part 30 residents of the Solidarity Inn of the Municipality of Loja, to whom a survey was applied like instrument of information gathering. The information was processed using the informatic program called Excel and the results were presented in tables, whose results showed that all the residents are men between 18 to 64 years, most of them from Loja, the most consumed psychoactive substances are alcoholic beverages, with a consume frequency weekly. The residents of this community have a dysfunctional family, being the dimensions also affected: harmony, permeability, affectivity and adaptability. So it could be concluded that the consumption of psychoactive substances should not only be addressed to the person who consumes, but integrally to the family too, thus determining the correlation between these two variables. Keywords: psychoactive substances, functional family, dysfunction, mental health